Impact of baseline body mass index on the efficacy and safety of tofacitinib in patients with psoriatic arthritis. Issue 1 (15th January 2021) - Giles, Jon T; Ogdie, Alexis; Gomez Reino, Juan J; Helliwell, Philip; Germino, Rebecca; Stockert, Lori; Young, Pamela; Joseph, Wael; Mundayat, Rajiv; Graham, Daniela; Ritchlin, Christopher
Abstract : Objectives: This post-hoc analysis explored the impact of body mass index (BMI) on tofacitinib efficacy/safety in patients with active psoriatic arthritis (PsA). Methods: Data were pooled from two phase 3 studies (NCT01877668 ; NCT01882439 ). Analyses included patients randomised to tofacitinib 5/10 mg twio times a day or placebo, stratified by baseline BMI: <25 kg/m 2, ≥25–<30 kg/m 2, ≥30–<35 kg/m 2 or ≥35 kg/m 2 . Endpoints (month 3): American College of Rheumatology (ACR20/50/70), Health Assessment Questionnaire-Disability Index (HAQ-DI) and Psoriasis Area and Severity Index (PASI) 75 response rates; dactylitis/enthesitis resolution rates; changes from baseline Short Form-36 Health Survey version 2 (SF-36v2) Physical/Mental Component Summary (PCS) scores and Functional Assessment of Chronic Illness Therapy-Fatigue (FACIT-F) total score. Safety was also reported. Results: Analysis included 710 patients; 43.8% were obese (BMI ≥30 kg/m 2 ). Tofacitinib demonstrated higher efficacy response rates at month 3, compared with placebo, regardless of baseline BMI. Generally, ACR20/50/70 and HAQ-DI response rates, enthesitis resolution rates and changes from baseline in SF-36v2 PCS score and FACIT-F total score (month 3) were reduced in patients with baseline BMI ≥35 kg/m 2 versus patients with lower BMIs. Elevated alanine aminotransferase/aspartate aminotransferase levels were reported in patients with baseline BMI ≥35 kg/m 2 receiving tofacitinib 5 mg but not 10 mg two times a day. Conclusion: Tofacitinib demonstrated greater efficacy than placebo in patients with PsA, regardless of baseline BMI. For all treatment arms, reduced efficacy was observed in patients with baseline BMI ≥35 kg/m 2 . Safety was generally comparable across BMI categories, although the effect of tofacitinib on liver enzymes in patients with baseline BMI ≥35 kg/m 2 was inconclusive.